TEKNOLOGI PEMBUATAN SILASE RUMPUT GAJAH DI JORONG JAMBAK NAGARI LINGKUANG AUA KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Nadia Saputri (LPPM Universitas Andalas, 2022)
Forage is the main feed for ruminants. Farmers in Jorong Jambak Nagari Lingkuang Aua, West Pasaman, only rely on forage that grows around the plantation; this, of course, cannot meet the nutritional needs of their livestock. The primary problem breeders face in this area is the availability of forage which does not meet the needs of their livestock. To overcome this problem, it is necessary to process forage feed with silage technology. Silage is an anaerobic feed preservation technique using silos. This activity aims to provide education and technology transfer to the public regarding the technology for making elephant grass silage to increase the productivity of ruminants in Jorong Jambak Nagari Lingkuang Aua, West Pasaman Regency. This activity was carried out in Jorong Jambak Nagari Lingkuang Aua, Pasaman District, West Pasaman Regency. The activity method is outreach/counseling and training in elephant grass silage making and evaluation. The activity targets breeders and the community in Jorong Jambak Nagari Lingkuang Aua, West Pasaman. The activity involved lecturers and students of the Faculty of Animal Husbandry, Andalas University. The results of the implementation of the exercise showed that farmers enthusiastically participated in implementing this activity. This activity can increase breeders' understanding, knowledge, and skills, and even breeders have been able to apply it to make silage from elephant grass which can support the productivity of ruminants. Preservation of forage/elephant grass silage can overcome the shortage of forage and ensure the availability of ruminant fodder in the dry season.